Pengembangan Media Pembelajaran Video Animasi Berbasis Keterampilan Proses Sains pada Pembelajaran IPA - Dwi Septiani; Prima Mutia Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The development of increasingly modern times, teachers are required to innovate regarding learning media. This study aims to develop learning media in the form of animated videos based on science process skills, on energy material for learning science in grade IV elementary schools. This research is a Research and Development (R&D) study by adopting the Borg and Gall development model which is carried out in seven stages, namely potentials and problems, data collection, product design, design validation, product design revisions, product trials and product revisions. Data collection techniques in this study used questionnaires and validation sheets. Data analysis using Likert scale analysis. Validation was carried out by material experts, media experts, and education experts. The trials were conducted in small groups of 7 students and large groups of 25 students. The results of this validation were carried out by material experts obtaining a score of 77% which was categorized as very suitable for use, media experts by 95%, who were categorized as very suitable for use, the results of trials on education experts obtained a score of 93.7% which were categorized as very suitable for use and students with small-scale group trials of 96.18%, large-scale group trials of 94.65%, with categories suitable for use. It can be concluded that animated video learning media based on science process skills is appropriate for use in class IV on natural science learning on energy sources. Keywords: Learning media, Animation, Energy Sources, Science